2015
DOI: 10.1152/ajprenal.00195.2015
|View full text |Cite
|
Sign up to set email alerts
|

Slow- and fast-twitch hindlimb skeletal muscle phenotypes 12 wk after ⅚ nephrectomy in Wistar rats of both sexes

Abstract: This study describes fiber-type adaptations in hindlimb muscles, the interaction of sex, and the role of hypoxia on this response in 12-wk ⅚ nephrectomized rats (Nx). Contractile, metabolic, and morphological features of muscle fiber types were assessed in the slow-twitch soleus and the fast-twitch tibialis cranialis muscles of Nx rats, and compared with sham-operated controls. Rats of both sexes were considered in both groups. A slow-to-fast fiber-type transformation occurred in the tibialis cranialis of Nx r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Evidence of slow-to-fast fiber-type transition was observed in the TC muscle of uremic rats that did not receive exogenous calcitriol but not in uremic rats receiving calcitriol. This result suggests that vitamin D treatment counteracts the fiber-type switching in the direction I¡IIA¡IIX¡IIB reported in fasttwitch hindlimb muscles in the course of uremic myopathy (1,5,36,52). In a small uncontrolled study, it was reported an increase in the percentage of type IIA fibers accompanied by a reduction of type IIB fibers in muscle biopsies from elderly women treated with calcitriol and calcium for 3-6 mo (51).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Evidence of slow-to-fast fiber-type transition was observed in the TC muscle of uremic rats that did not receive exogenous calcitriol but not in uremic rats receiving calcitriol. This result suggests that vitamin D treatment counteracts the fiber-type switching in the direction I¡IIA¡IIX¡IIB reported in fasttwitch hindlimb muscles in the course of uremic myopathy (1,5,36,52). In a small uncontrolled study, it was reported an increase in the percentage of type IIA fibers accompanied by a reduction of type IIB fibers in muscle biopsies from elderly women treated with calcitriol and calcium for 3-6 mo (51).…”
Section: Discussionmentioning
confidence: 96%
“…Afterwards, rats were randomly allocated to the following groups with balanced sexes: sham-operated control (So; n ϭ 24) and 5/6 nephrectomy (Nx, n ϭ 36 rats). The Nx was carried out following a two-step procedure that reduces the original renal mass by five-sixths as previously described (1). The control So rats were sham operated with the same protocol and total duration of the surgery, except both kidneys were maintained intact.…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations